Triglyceride-Glucose Index as A Crucial Marker for Polycystic Ovary Syndrome Women with Insulin Resistance - Hestiantoro, Andon; Saraswati, Jaya; Prasetya, David Eka; Sandra, Ferry; Muharam, Raden; Pratama, Gita; Harzif, Achmad Kemal (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Insulin resistance (IR) is considered as the main driver of polycystic ovary syndrome (PCOS) pathogenesis. In PCOS condition, IR is frequently related to glucose, anthropometric profile, lipid profile, and hormone profile parameters. However, not all PCOS phenotype show IR. Therefore, this study was conducted to determine the association the parameters mentioned above in PCOS subjects with and without IR.METHODS: Fifty PCOS women with IR and 26 PCOS women without IR were recruited. All subjects underwent physical examination for measurement of weight, waist circumference (WC), and body mass index (BMI). Ferriman Gallwey Score (FGS) was used to evaluate hirsutism. Blood sample was taken from each subject for measurement of fasting glucose, postprandial glucose, fasting insulin, low-density lipoprotein (LDL), high-density lipoprotein (HDL), total cholesterol, triglyceride (TG), sex hormone binding globulin (SHBG), thyroid-stimulating hormone (TSH), luteinizing hormone (LH), follicle stimulating hormone (FSH), and prolactin. Homeostatic model assessment for IR (HOMA-IR), TG-glucose index (TyGI), and free testosterone index (FTI) were then calculated.RESULTS: From all the parameters examined, only fasting insulin (p<0.001), HOMA-IR (p<0.001), SHBG (p=0.012), TG (p<0.001), and TyGI (p=0.008) that show significant differences between PCOS subjects with and without IR. After multivariate analysis, TyGI was found to have strong association with IR occurrence in PCOS subjects (p=0.005) with an odd ratio of 5.26 (1.65–16.74).CONCLUSION: TyGI appears to have a significant association with the IR occurrence in PCOS subjects. Hence, it can be suggested that TyGI could be an important marker for PCOS women with IR.KEYWORDS: insulin resistance, lipid metabolism, polycystic ovary syndrome, triglyceride-glucose index